Pengaruh Free Cash Flow, Leverage, Konservatisme Akuntansi dan Kompensasi Eksekutif Terhadap Manajemen Laba - Nurmaya, Maya; Purnama, Dendi; Nurfatimah, Siti Nuke (Department of Accounting, Faculty of Economics & Business, 2025)
The purpose of this research to analyze and prove empirical facts and produce a model that can explain the influence of free cash flow, leverage, accounting conservatism and executive compensation on earnings management. The population in this research is 76 energy sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique used purposive sampling technique, so that the final sample obtained was 44 companies or 220 observation data. The data analysis technique used is panel data regression analysis. The results showed that leverage and executive compensation have a positive and significant effect on earnings management, accounting conservatism has a negative and significant effect on earnings management, while free cash flow has a positive and insignificant effect on earnings management.